Empirical Analysis of Non Performing Assets Related to Private Banks of India - Mehta, Laveena; Malhotra, Meenakshi (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
In present scenario, Indian banks are struggling with challenges related with NPA’s. Some years before these banks were in Flourishing heights.but health of these banks deteriorated because of non performing assets. Many Indian banks have been controlled their non performing assets up to a level, but some banks still have been failed to control their NPA’s status, as a result, NPA hitting the profitability of these banks. Through this research paper we have examined the trend of NPA’s over the past 8 years and the relationship between NPA’s and profitability of private sector banks. According to the Reserve bank of India priority sector lending must be promoted so that those sectors who can’t approach the organized market for lending purposes and can’t afford the higher commercial rate of interest, can get loans in an easy way. RBI specified the percentage of loans to priority sectors out of the total money lent by the banks. This paper examines the NPA in Priority Sector Lending and the impact of priority sector lending on the gross NPA of private sector banks. The result showed the significant impact of priority sector lending on gross NPA of private Sector banks. This study revolves between the period 2005 and 2012.